THE INTERREGIONAL FLOW OF FUNDS IN THE UNITED STATES, 1955–58* - Kane, Edward J. (Journal of Finance, 1962)
Thesis: Ph. D., Massachusetts Institute of Technology, Department of Economics and Social Science, 1960